Induction of Synovitis Using Interleukin-1 Beta: Are There Differences in the Response of Middle Carpal Joint Compared to the Tibiotarsal Joint? - Colbath, Aimee C.; Dow, Steven W.; Hopkins, Leone S.; Phillips, Jennifer N.; McIlwraith, C. Wayne; Goodrich, Laurie R. (Frontiers in Veterinary Science, 2018)
Abstract: Background: The effects of recombinant interleukin-1β (rIL-1β) have been described for the middle carpal joint (MCJ). However, we are unaware of any studies that have described the cytological response of the tibiotarsal joint (TTJ) to rIL-1β or compared the clinical and cytological responses of the MCJ to the TTJ following the administration of intra-articular rIL-1β. Such information is critical for researchers planning to use rIL-1β to create acute synovitis models in horses. Objectives: To compare the clinical and cytological responses of the MCJ to the TTJ following administration of intra-articular rIL-1β. Methods: Twelve horses were used for the study. Eight horses received 75ng of rIL-1β into the MCJ and four horses received 75ng of rIL-1β into the TTJ. Clinical and cytological outcome parameters including lameness, joint circumference, joint effusion score, total nucleated cell count, cellular differentials, C-reactive protein and prostaglandin-E2 concentrations were determined at baseline and multiple post-treatment time points over a 336-hour period (2 weeks). Results: Recombinant IL-1β administered into the TTJ resulted in a significantly greater respiratory rate at 24 hours and heart rate at 12 hours when compared to rIL-1β administered into the MCJ. In addition, the TTJ had a significantly greater increase in joint circumference at 24 post-injection hour (PIH) and subjective effusion grade at 24 PIH and 336 PIH. The MCJ had significantly higher total protein concentration at 6 PIH, and a significantly higher NCC at 24 and 72 PIH when compared to the TTJ. Conversely, the TTJ had significantly higher neutrophilic infiltration than the MCJ at 6 PIH and 168 PIH. Conclusions: This study establishes that the same intra-articular dose of rIL-1 β elicits significantly different clinical and cytological responses in the MCJ compared to the TTJ in the equine model of intra-articular synovitis. In addition, clinical and cytological evidence of synovitis may persist up to or greater than 1 week following intra-articular administration of rIL-1 β.